Validation of WHOQOL-BREF to measure quality of life among women with polycystic ovary syndrome - V. Kumarapeli; R. de A. Seneviratne; C. N. Wijeyaratne (College of Community Physicians of Sri Lanka, 2006)
Introduction Symptoms typically associated with polycystic ovary syndrome (PCOS) such as oligo/ amenorrhoea, hirsutism, obesity, subfamily lead to a significant reduction in quality of life (QOL). At present, no validated questionnaire exists to measure the QOL of women with PCOS. The study was carried out to validate WHOQOLBREF before its application to assess quality of life in women with PCOS in Sri Lanka.   Methodology The WHOQOL-BREF was validated on 130 women with PCOS attending an endocrine clinic at a tertiary care hospital and 130 community controls. Both convergent and discriminant validity of WHOQOL-BREF were measured simultaneously using the Multitrait-Multimethod Matrix technique in comparison with SF 36. Confirmatory factor analysis using principal component analyses was performed 10 test the construct validity. Reliability was measured by assessing internal consistency and Lest-retest reliability.   Results Good convergent and discriminant validity was demonstrated by the WHOQOL-BREF for similar and different scales respectively in comparison with SF-36. Internal consistency measured using Cronbach's alpha exceeded Nunnaly's criteria of 0.7 for all except the social relationship domain in both groups while the test retest reliability measured using Pearson's correlation coefficients exceeded >0.7 (p<0.01) in all domains.   Conclusions WHOQOL-BREF was found to be a valid and a reliable tool to assess QOL of women with PCOS. It showed good convergent validity, discriminant validity and reliability in all except the social relationships domain.